Literature Review: Implementation of Patient Safety Goals in Hospitals in Indonesia - Andryani Larasati; Inge Dhamanti (Universitas Airlangga, 2021)
Background: The implementation of a good patient safety system in the hospital aims to minimize and prevent patient safety incidents. The patient safety goals is a system that aims to encourage specific improvements in patient safety. Patient safety goals are actions that must be taken by the hospital to prevent patient safety incidents that can harm patients and the hospital. Purpose: Writing this review article aims to provide an overview of the implementation of patient safety goals in hospitals in Indonesia.Methods: The method used in this article is a literature review. Article searches were conducted through Google Scholar and Portal Garuda with the keywords